Radiolabeling and In-Silico Study of 131I-(4-fluorobenzoyl-3-methylthiourea) as Radiopharmaceuticals for Breast Cancer Theranostics - Pratama, Febby; Ruswanto, Ruswanto; Nofianti, Tita; Pratita, Anindita Tri Kusuma; Daruwati, Isti; Susilo, Veronika Yulianti; Holik, Holis Abdul (Syarif Hidayatullah State Islamic University, 2024)
The chemicals produced from thiourea are actively being studied as anticancer possibilities. In complexes with radionuclides like Iodine-131, the 1-(4-Fluorobenzoyl)-3-methyl thiourea is a promising ligand for theragnostic applications. This study aimed to label 1-(4-fluorobenzoyl-3-methylthiourea) with iodine-131 and observe its interaction with breast cancer receptors. The radiolabeling of 131I-(4-fluorobenzoyl-3-methylthiourea) uses the radioiodination method with Chloramine-T, and an in-silico investigation of breast cancer receptors was conducted. According to the results of molecular docking using AutoDockTools, this radiopharmaceutical molecule has the best activity on the HER2 receptor (PDB ID: 3PP0) compared to the native ligand and control positive, with a binding affinity of -6.13 kcal/mol and a Ki value of 32.05 mM. According to the molecular dynamics data using Desmond, the radiopharmaceutical molecule 131I-(4-Fluorobenzoyl-3-methylthiourea) displays good stability starting from the 50ns range. The indirect radioiodination method has successfully labeled 1-(4-Fluorobenzoyl-3-methylthiourea) with iodine-131.